HUBUNGAN ANTARA TINGKAT LITERASI AL QURAN DENGAN HASIL BELAJAR AGAMA ISLAM - Muzakkir, Muzakkir; Mappasiara, Mappasiara; Dani, Ali Umar (Universitas Islam Negeri Alauddin Makassar, 2021)
The purpose of this study is to know the relationship of the level of reading of the Quran with the results of studying Islam students of SMA Negeri 10 Gowa. This research field research initiative is descriptive quantitative with causal associative methods. Simple sampling technique random sampling with a sample number of 60 students. Learners who test read The Quran score: Melafadzkan value so makhrajnya get an average score of 3.5; Melafadzkan Value since its nature get a flat value of 3.1; Melafadz kan Kekkahan with law readings average value of 3.0; and Read the Quran smoothly the average value of 3.3. Based on the criteria of the decision decision, then H0 is accepted and Ha abroad there is no literacy relationship between the literacy of the Quran and the results of learning PAI at SMA Negeri 10 Gowa.